Efektivitas Penerapan Sistem dan Prosedur Akuntansi Aset Tetap pada Dinas Perdagangan dan Perindustrian Kabupaten Sukabumi - Andrawan, Vikri; Kartini, Tina; Nurmilah, Risma (Ikatan Da'i Indonesia, 2024)
This study aims to evaluate the effectiveness of the implementation of fixed asset accounting systems and procedures at the Trade and Industry Office of Sukabumi Regency. The research method used is a qualitative method with an analytical descriptive approach. Data were collected through interviews, observations, and documentation. The results showed that the implementation of fixed asset accounting systems and procedures is in accordance with applicable government accounting standards, but there are still some obstacles in its implementation such as lack of training for staff and limited resources. Based on the calculation of the effectiveness ratio using the Dean J. Champion measuring instrument, the effectiveness level reached 88%, which is included in the very effective category. The number of indicators assessed were 11 indicators of fixed asset accounting systems, with 9 indicators met, and 7 indicators of fixed asset accounting procedures, which were all met. Recommendations to improve effectiveness include providing better training for staff, increased resource allocation, and improved management and internal controls.